Design of Augmented Reality Interactive Learning Media in Learning Sundanese Fairy Tales - Dzakiah, Shoofii Nurrizki; Nugraha, Haris Santosa; Kosasih, Dede; Widyastuti, Temmy (Teknodika, 2024)
Fairy tales contain noble values that can shape students' characters. Specifically, students' ability to understand Sundanese fairy tales currently tends to be low due to the increasing rarity of Sundanese being used in everyday life. For this reason, it is necessary to involve technology-based media that is interesting and able to increase motivation to learn fairy tales. The purpose of this research is to describe the needs analysis, design, and testing of augmented reality learning media development in Sundanese fairy tale material. The method used in this research was the R&D research method with the ADDIE model. The participants involved in this study included two experts (media and literature learning), six Sundanese language teachers, and 24 elementary school students. The research instruments employed were questionnaires, interviews, and tests. The resulting data were then processed using quantitative descriptive techniques, which were then interpreted qualitatively. The results revealed three things: 1) there was a need for the development of fairy tale learning media using augmented reality media; 2) augmented reality media was designed through three stages, namely formulating media concepts (selection of fairy tales and analysis of fairy tale characteristics), designing storyboards (visualization of plot, setting, and characters), and preparing and determining design components using the assemblr EDU application; and 3), the results of expert validity of the augmented reality media design developed could be categorized as very good, with an average percentage of feasibility reaching 92.4%. The implications of using augmented reality media can color the use of digital media in Sundanese language learning as an alternative solution to improving students' ability to understand Sundanese fairy tales.